Pengaruh Cekaman Aluminium terhadap Kandungan Asam Organik dalam Kalus dan Pinak Tomat (Lycopersicon esculentum Mill.) - Wening Enggarini; Erly Marwani (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
The purpose of this research was to evaluate the effects of Al stress on citric, malic and oxalic acid content of L. esculentum cv. Intan callus and plantlet, also aluminum content of L. esculentum plantlet. Callus was induced from cotyledone of L. esculentum on Murashige & Skoog (MS) media containing 10-7 M NAA and 10-6 kinetin. The callus was then transferred step wisely at 3 weeks interval to media containing 220, 275, 330, 385, 440, 550, 825, and 1100 μM AlCl3. The callus cultures on the control media and media with the addition of 550 μM AlCl3 were able to regenerate and produce shoots after 8 passages of subculture. The shoots from media with the addition of 550 μM AlCl3 were transferred into the media with addition of 825 μM AlCl3, then to the media with 1100 μM AlCl3. The High Pressure Liquid Chromatography (HPLC) analysis showed that Al stress callus and plantlets contained malic acid, but no citric and oxalic acid. The content of malic acid in callus decreased with increasing AlCl3 concentration from 0 to 385 μM. On the other hand, the content of malic acid in callus increased with increasing AlCl3 concentration from 440 μM to 1100 μM. Similarly, the content of malic acid in root increased with increasing concentration of AlCl3 from 550 μM to 1100 μM. The result of Neutron Activation Analysis showed that Al content in root decreased as the amount of AlCl3 increased in the media. These results suggested that L. esculentum callus and plantlet respond to the Al stress by producing higher amount of malic acid.